Epidemiological characteristics of hereditary motor and sensory neuropathy in the Sumy region - Govbakh, Iryna; Mishchenko, Tamara (ScienceRise: Medical Science, 2023)
The aim of the study was to investigate the characteristics of the spread of hereditary motor and sensory neuropathy type 1A in the Sumy region, in terms of administrative units and specific ethnic groups of the population. Materials and methods. An epidemiological study of hereditary motor and sensory neuropathy (HMSN) type 1A in the Sumy region was conducted based on patient referrals to various healthcare facilities from 2014 to 2017. The prevalence of HMSN in the Sumy region was studied using an epidemiological approach. The prevalence rate of HMSN was calculated for different administrative units of the Sumy region, as well as for specific ethnic groups of the population. Results. The study registered 67 patients with hereditary motor and sensory neuropathy type 1A in the Sumy region. The prevalence rate of hereditary motor and sensory neuropathy type 1A in the Sumy region was 5.96 per 100,000 population. Of the HMSN patients, 47.8 % (32 individuals) resided in urban areas, while 52.2 % (35 individuals) lived in rural areas. In terms of gender distribution, 59.7 % (40 individuals) were female, and 40.3 % (27 individuals) were male. Most patients were of Ukrainian ethnicity (77.6 %), followed by Russians (20.9 %). Belarusians accounted for 1.5 % of HMSN patients in the Sumy region. Among other ethnic groups present in the Sumy region, HMSN type 1A was not detected. Conclusions. Hereditary motor and sensory neuropathy type 1A is unevenly distributed in the Sumy region. The heterogeneous distribution of the disease is primarily attributed to the characteristics of settlement in specific geographic regions, which have led to the formation of territorial, national, and religious isolates with the accumulation of genetically heterogeneous types in these populations, resulting in an increased genetic burden